1999
DOI: 10.1007/s00585-999-0838-2
|View full text |Cite
|
Sign up to set email alerts
|

MUREX: a land-surface field experiment to study the annual cycle of the energy and water budgets

Abstract: Abstract. The MUREX (monitoring the usable soil reservoir experimentally) experiment was designed to provide continuous time series of field data over a long period, in order to improve and validate the Soil-vegetation-Atmosphere Transfer (SVAT) parameterisations employed in meteorological models. Intensive measurements were performed for more than three years over fallow farmland in southwestern France. To capture the main processes controlling land-atmosphere exchanges, the local climate was fully characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 31 publications
(19 reference statements)
0
28
0
Order By: Relevance
“…Even if the surface heat storage can be at a maximum during spring over midlatitudes, it does not seem physical that the spring heat storage is largely superior to the summer rate. During the MUREX experiment (43°24′N, 1°10′E), a fallow site similar to SMOSREX, Calvet et al [1999] showed that the spring heat storage is not so different than the summer rate.…”
Section: Surface Energy Fluxesmentioning
confidence: 99%
“…Even if the surface heat storage can be at a maximum during spring over midlatitudes, it does not seem physical that the spring heat storage is largely superior to the summer rate. During the MUREX experiment (43°24′N, 1°10′E), a fallow site similar to SMOSREX, Calvet et al [1999] showed that the spring heat storage is not so different than the summer rate.…”
Section: Surface Energy Fluxesmentioning
confidence: 99%
“…The root biomass was not measured at SMOSREX. Over the grassland of the MUREX site, located in the same region as SMOSREX, most roots were found in the 0.25 m surface soil layer and few roots were observed in deeper layers, down to 0.70 m (Calvet et al, 1999). It must be noted that, in this study, a simple force-restore version of the model hydrology is used.…”
Section: Soil Moisturementioning
confidence: 99%
“…The satellite data we will use are essentially sensitive to the surface top (the penetration depth is usually of the order of the observed wavelength). We checked on ancillary data sets providing a detailed description of the vertical soil moisture profiles [ Calvet et al , 1999; Wigneron et al , 1995] that the surface top moisture (∼0.5 cm) is rather well correlated with the 10 cm layer moisture, even at small timescales (correlation of at least 0.6 for the 4 analyzed locations with daily measurements). When averaged over the month, even larger correlations are expected.…”
Section: Data Sourcesmentioning
confidence: 99%